The green vaccine -The future of preventive medicine and dentistry? - R Siddana Goud; Shoba Fernandes; D Prabu; Vidhatri Tiwari; Shrudha Potdar (Wolters Kluwer Medknow Publications, 2013)
The tremendous impact of plant based products is evident in every facet of human lives. The progress of science has resulted in developing transgenic plants which would prove to be a boon when translated into edible vaccines. Such vaccines would bring about wide reaching changes in the prevention of an array of diseases because of their accessibility and economic viability. Cautious production of edible vaccines under stringent guidelines would endow developing nations with innumerable advantages in disease prevention.